The practice of catheter cryoablation for cardiac arrhythmias - Chan, Ngai-Yin.; ebrary, Inc. (Chichester, West Sussex, U.K. : John Wiley & Sons, 2014)
"A comprehensive guide, with self-assessment to the clinical application of this exciting alternative treatment for atrial fibrialtion and other cardiac arrhythmias"--Provided by publisher.
Machine generated contents note: List of Contributors Preface Acknowledgements About the companion website 1 Biophysical Principles and Properties of Cryoablation / Hung-Fat Tse and Jo Jo Hai -- 2 Catheter Cryoablation for Pediatric Arrhythmias / George F. Van Hare and Kathryn K. Collins -- 3 Atrioventricular Nodal Re-entrant Tachycardia: What Have we Learned From Radiofrequency Catheter Ablation ? / Ruey J. Sung, Charlie Young and Michael R. Lauer -- 4 Catheter Cryoablation for Atrioventricular Nodal Re-entrant Tachycardia / Ngai-Yin Chan -- 5 Cryoballoon Pulmonary Vein Isolation for Atrial Fibrillation / Jurgen Vogt -- 6 Prevention of Phrenic Nerve Palsy During Cryoballoon Ablation for Atrial Fibrillation / Marcin Kowalski -- 7 Linear Isthmus Ablation for Atrial Flutter: Catheter Cryoablation versus Radiofrequency Catheter Ablation / Gregory K. Feld and Navinder Sawhney -- 8 Catheter Cryoablation for the Treatment of Accessory Pathways / Ngai-Yin Chan -- 9 Catheter Cryoablation for the Treatment of Ventricular Arrhythmias / Luigi Di Biase, Xue Yan, Pasquale Santangeli, Amin Al-Ahamad, Henry H. Hsia, David J. Burkhardt, Andrea Natale -- 10 Catheter Cryoablation for the Treatment of Miscellaneous Arrhythmias / Ngai-Yin Chan. Index .
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Arrhythmia -- Cryosurgery; Electronic books